Dabigatran or Aspirin in East Asian Patients With Embolic Stroke of Undetermined Source: RE-SPECT ESUS Subgroup Analysis. Issue 3 (16th February 2021) - Uchiyama, Shinichiro; Toyoda, Kazunori; Lee, Byung-Chul; Liou, Chia-Wei; Wong, Lawrence Ka Sing; Grauer, Claudia; Brueckmann, Martina; Taniguchi, Atsushi; Urano, Yasuhisa; Easton, J. Donald; ,
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: We assessed the outcomes of dabigatran versus aspirin in a prespecified subgroup analysis of East Asian patients with embolic stroke of undetermined source in the RE-SPECT ESUS trial (Randomized, Double-Blind, Evaluation in Secondary Stroke Prevention Comparing the Efficacy and Safety of the Oral Thrombin Inhibitor Dabigatran Etexilate Versus Acetylsalicylic Acid in Patients With Embolic Stroke of Undetermined Source). Methods: Patients with a recent embolic stroke of undetermined source were randomized to dabigatran (150 or 110 mg BID) or aspirin (100 mg QD). The primary efficacy outcome was recurrent stroke; the primary safety outcome was major bleeding. The East Asia cohort was compared with patients from all other countries (non-East Asia cohort). Results: Overall, 988 of 5390 patients (18%) were randomized in East Asia. During a median follow-up of 18.8 months, there was no statistically significant difference in recurrent stroke (hazard ratio, 0.65 [95% CI, 0.41–1.03]) or major bleeding (hazard ratio, 1.04 [95% CI, 0.57–1.91]) in East Asian patients receiving dabigatran versus aspirin. Death from any cause occurred more often in the dabigatran versus the aspirin group (hazard ratio, 3.98 [95% CI, 1.32–12.01]). Conclusions: The treatment effect of dabigatran versus aspirin was consistent between cohorts, with no apparent superiority for dabigatran over aspirin in preventing recurrent stroke in patients with embolic stroke of undetermined source. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02239120.